Negative electrode material, negative electrode plate and battery

By adding an appropriate amount of elastic conductive particles to the silicon-based negative electrode material, the problem of excessive expansion rate of the silicon-based negative electrode during charging and discharging is solved, and the effect of reducing the electrode expansion rate and improving the battery cycle stability is achieved.

CN119764424APending Publication Date: 2025-04-04CHINA AUTOMOTIVE BATTERY RES INST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510011333.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the silicon-based negative electrode has a problem of excessive expansion rate during charging and discharging, resulting in deterioration of battery performance.

Method used

The elastic conductive particles are added to the negative electrode active material, and the ratio between the D50 of the elastic conductive particles and the D50 of the negative electrode active material is 1:1 to 8, and the mass proportion of the elastic conductive particles in the negative electrode active material does not exceed 16.67%, so as to absorb and disperse the stress caused by the volume change of the negative electrode active material.

Benefits of technology

It effectively reduces the expansion rate of the electrode, reduces the attenuation of the negative electrode capacity, and improves the cycle stability and capacity retention rate of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764424A_ABST
    Figure CN119764424A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material, a negative electrode plate and a battery. The negative electrode material comprises a negative electrode active material and elastic conductive particles, the ratio of D50 of the elastic conductive particles to D50 of the negative electrode active material is 1: 1-8, and the mass ratio of the elastic conductive particles in the negative electrode active material does not exceed 16.67%. By controlling the ratio of the D50 of the elastic conductive particles to the D50 of the negative electrode active material to be 1: 1-8, the volume expansion stress generated by the negative electrode active material in the charging and discharging process can be absorbed and relieved. The mass ratio of the elastic conductive particles in the negative electrode active material is controlled not to exceed 16.67%, so that the stress slow release effect is ensured, and excessive influence on the energy density of the battery is avoided. By introducing the elastic conductive particles, the stress caused by the volume change of the negative electrode active material in the charging and discharging process is favorably absorbed and dispersed, so that the cycle stability and the capacity retention ratio of the battery are favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode material, a negative electrode sheet and a battery. Background Art

[0002] Lithium metal and silicon are candidate anode materials for all-solid-state lithium-ion batteries (ASSBs) due to their high specific capacity, among which silicon-based materials have the highest theoretical specific capacity (4200 mAh g -1 ) and low potential (0.3Vvs.Li + / Li), and compared with lithium metal, silicon is abundant in resources, low in cost, and easy to process. It is thermodynamically stable with solid electrolytes. Therefore, silicon-based materials provide the possibility for the design of high-energy-density batteries. However, the huge volume change of silicon negative electrode during charging and discharging leads to the degradation of battery performance and affects the scale of use. At present, the main strategic methods to alleviate the volume change of silicon negative electrode are through material design, electrode structure design and battery structure design.

[0003] The Chinese patent application with the patent application publication number CN115663188A discloses a negative electrode, which alleviates the volume expansion effect of the silicon-based negative electrode by grading short carbon nanotubes with low aspect ratio and containing hydroxyl groups and long carbon nanotubes with high aspect ratio and containing carboxyl groups. However, the negative electrode has limited improvement on the high gram capacity silicon-based negative electrode and cannot dissipate the electrode stress well.

[0004] The Chinese patent application with the patent application publication number CN116169277A discloses a silicon negative electrode, which forms silicon or silicon oxide nanopowder by ball milling and nano sand milling, and then mixes with artificial graphite micron, adds organic matter and anneals at high temperature to obtain carbon-coated composite particles. However, since the elasticity of graphite and silicon negative electrodes is similar, they cannot absorb the electrode expansion stress to the maximum extent, and the improvement is limited.

[0005] The Chinese patent application with the patent application publication number CN106848190A discloses a negative electrode structure, including a base coat, a middle coat and a top coat sequentially coated on the surface of the current collector, the base coat, the middle coat and the top coat are coated with a slurry including a negative electrode active material, a conductive agent, a thickener and a binder; the binder in the base coat and the middle coat is a water-based slurry binder, and the content of the binder in the middle coat is less than the content of the binder in the base coat, so as to alleviate the expansion of the electrode. The method is complex and requires the preparation of a variety of different slurries, and has high requirements for production processes and equipment.

[0006] The battery is assembled by increasing the current in parallel, increasing the voltage in series and stacking, and is charged and discharged under a certain external pressure. During the charging and discharging process, the volume expansion of the silicon negative electrode material causes increased stress, which destroys the stability of the electrode and battery structure. The currently disclosed patents and literature have alleviated the expansion problem of low-gram capacity silicon-based composite negative electrodes to a certain extent, but have no significant effect on reducing the expansion of silicon-based composite negative electrodes with a gram capacity of ≥500mAh / g. Summary of the invention

[0007] The main purpose of the present invention is to provide a negative electrode material, a negative electrode sheet and a battery to solve the problem of excessively high expansion rate of silicon-based negative electrodes during charging and discharging in the prior art.

[0008] In order to achieve the above-mentioned object, according to one aspect of the present invention, a negative electrode material is provided, which includes a negative electrode active material and elastic conductive particles, the ratio of D50 of the elastic conductive particles to D50 of the negative electrode active material is 1:1 to 8, and the mass proportion of the elastic conductive particles in the negative electrode active material does not exceed 16.67%.

[0009] Furthermore, the ratio of D50 of the elastic conductive particles to D50 of the negative electrode active material is 1:3-6.

[0010] Furthermore, the mass ratio of the elastic conductive particles to the negative electrode active material is 1:10-20.

[0011] Furthermore, the average elastic modulus of the elastic conductive particles is 0.1-600 MPa; and / or the average electrical conductivity of the elastic conductive particles is 1000-100000 S / m.

[0012] Furthermore, the elastic conductive particles include elastic particles and a conductive layer coated on the surface of the elastic particles, and the mass proportion of the conductive layer in the elastic conductive particles does not exceed 1%.

[0013] Furthermore, the material of the elastic particles is selected from any one or more of thermoplastic elastomers, thermoplastic rubbers, thermoplastic vulcanized rubbers, thermoplastic polyurethane elastomers, thermoplastic polyolefin elastomers and thermoplastic polyester elastomers; and / or the material of the conductive layer is selected from any one or more of carbon nanotubes, vapor-grown carbon fibers and graphene.

[0014] Furthermore, the elastic particles include first elastic particles and second elastic particles, the mass ratio of the first elastic particles to the second elastic particles is 1:1-4, the material of the first elastic particles is thermoplastic polyurethane elastomer, and the material of the second elastic particles is thermoplastic rubber.

[0015] Furthermore, the D50 of the negative electrode active material is 2 μm to 35 μm; and / or the gram capacity of the negative electrode active material is not less than 420 mAh / g; and / or the negative electrode active material is selected from any one or more of silicon oxygen carbon, silicon carbon and micron silicon.

[0016] According to another aspect of the present invention, a negative electrode sheet is provided, wherein the negative electrode sheet contains the negative electrode material mentioned above.

[0017] According to another aspect of the present invention, a battery is provided, comprising a positive electrode sheet, an electrolyte, and a negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet mentioned above.

[0018] By applying the technical solution of the present invention, elastic conductive particles are added to the negative electrode active material, which helps to absorb and disperse the stress caused by the volume change of the negative electrode active material during the charge and discharge process, thereby helping to reduce the expansion rate of the electrode, and then helping to reduce the attenuation of the negative electrode capacity. By controlling the ratio of the D50 of the elastic conductive particles to the D50 of the negative electrode active material to 1:1 to 8, it helps to further absorb and relieve the volume expansion stress generated by the negative electrode active material during the charge and discharge process. By controlling the mass proportion of elastic conductive particles in the negative electrode active material to not more than 16.67%, the stress relief effect is guaranteed and excessive influence on the battery energy density is avoided. In short, the present application helps to absorb and disperse the stress caused by the volume change of the negative electrode active material during the charge and discharge process by introducing elastic conductive particles, thereby helping to improve the cycle stability and capacity retention rate of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0020] Figure 1 A schematic diagram of the structure of the elastic conductive particles of the present application is shown;

[0021] Figure 2 A schematic structural diagram of the battery of the present application is shown.

[0022] The above drawings include the following reference numerals:

[0023] 101, elastic particles; 102, conductive layer; 100, negative electrode sheet; 200, ion-conducting electronic insulating layer; 300, positive electrode sheet. DETAILED DESCRIPTION

[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0025] As analyzed in the background technology of this application, in the prior art, silicon-based negative electrodes have the problem of excessively high expansion rate during the charging and discharging process. In order to solve the above problem, this application provides a negative electrode material, a negative electrode sheet and a battery.

[0026] In a typical embodiment of the present application, a negative electrode material is provided, which includes a negative electrode active material and elastic conductive particles, the ratio of D50 of the elastic conductive particles to D50 of the negative electrode active material is 1:1 to 8, and the mass proportion of the elastic conductive particles in the negative electrode active material does not exceed 16.67%.

[0027] Adding elastic conductive particles to the negative electrode active material helps to absorb and disperse the stress caused by the volume change of the negative electrode active material during the charge and discharge process, thereby helping to reduce the expansion rate of the electrode, and then helping to reduce the attenuation of the negative electrode capacity. By controlling the ratio of the D50 of the elastic conductive particles to the D50 of the negative electrode active material to 1:1 to 8, it helps to further absorb and relieve the volume expansion stress generated by the negative electrode active material during the charge and discharge process. By controlling the mass proportion of elastic conductive particles in the negative electrode active material to not more than 16.67%, the stress relief effect is guaranteed and excessive impact on the battery energy density is avoided. In short, the present application helps to absorb and disperse the stress caused by the volume change of the negative electrode active material during the charge and discharge process by introducing elastic conductive particles, thereby helping to improve the cycle stability and capacity retention rate of the battery.

[0028] In order to better absorb and disperse the stress caused by the volume change of the negative electrode active material, in one embodiment of the present application, the ratio of D50 of the elastic conductive particles to D50 of the negative electrode active material is preferably 1:3-6.

[0029] In order to further ensure the stress relief effect and avoid the influence of the elastic conductive particles on the battery energy density, in one embodiment of the present application, the mass ratio of the elastic conductive particles to the negative electrode active material is preferably 1:10-20.

[0030] In one embodiment of the present application, the average elastic modulus of the elastic conductive particles is 0.1-600 MPa; and / or the average electrical conductivity of the elastic conductive particles is 1000-100000 S / m.

[0031] Elastic conductive particles with the above elastic modulus range are more suitable for being added to negative electrode active materials to absorb and disperse the volume expansion stress generated by the negative electrode active materials during the charging and discharging process; elastic conductive particles with the above conductivity range help to control the conductivity of the negative electrode material to maintain a larger value, thereby helping to improve the rate performance of the battery.

[0032] In one embodiment of the present application, Figure 1 As shown, the elastic conductive particles include elastic particles 101 and a conductive layer 102 coated on the surface of the elastic particles 101 , and the mass proportion of the conductive layer in the elastic conductive particles does not exceed 1%.

[0033] The role of the elastic particles is to absorb and disperse the generated stress, and the role of the conductive layer is to provide conductivity to ensure that the negative electrode material has a high conductivity, thereby helping to control the rate performance of the battery. It is preferred to control the mass proportion of the conductive layer in the elastic conductive particles to not exceed 1%, which helps to improve the structural stability of the elastic conductive particles while controlling the elastic conductive particles to have a high elastic modulus.

[0034] In one embodiment of the present application, the material of the elastic particles is selected from any one or more of thermoplastic elastomer (TPE), thermoplastic rubber (TPR), thermoplastic vulcanized rubber (TPV), thermoplastic polyurethane elastomer (TPU), thermoplastic polyolefin elastomer (TPO) and thermoplastic polyester elastomer (TPEE); and / or, the material of the conductive layer is selected from any one or more of carbon nanotubes (CNT), vapor grown carbon fiber (VGCF) and graphene, and it is further preferred that the material of the conductive layer is carbon nanotubes and / or vapor grown carbon fiber.

[0035] Preferably, the material type of the elastic particles is controlled within the above range, which helps to improve the stability and elastic modulus of the elastic particles, thereby helping to improve the ability to absorb and disperse stress. Preferably, the material type of the conductive layer is controlled within the above range, which helps to improve the interaction between the conductive layer and the elastic particles, thereby helping to further improve the conductivity of the elastic conductive particles.

[0036] In one embodiment of the present application, the elastic particles include first elastic particles and second elastic particles, the mass ratio of the first elastic particles to the second elastic particles is 1:1-4, and the material of the first elastic particles is thermoplastic polyurethane elastomer, and the material of the second elastic particles is thermoplastic rubber.

[0037] It is preferred to control the mass ratio of the first elastic particles to the second elastic particles within the above range, which helps to give full play to the synergistic effect between the two, thereby helping to further improve the ability of the elastic particles to absorb and disperse stress, and further help to improve the cycle stability and capacity retention rate of the battery.

[0038] In one embodiment of the present application, the D50 of the above-mentioned negative electrode active material is 2μm~35μm; and / or, the gram capacity of the negative electrode active material is not less than 420mAh / g; and / or, the negative electrode active material is selected from any one or more of silicon oxygen carbon, silicon carbon and micron silicon.

[0039] Since the elastic conductive particles of the present application have good adaptability, they can be adapted to the negative electrode active materials of the above types and characteristics.

[0040] In another typical embodiment of the present application, a negative electrode sheet is provided, wherein the negative electrode sheet contains the aforementioned negative electrode material.

[0041] Since the negative electrode sheet contains the elastic conductive particles of the present application, the negative electrode sheet has a lower expansion rate and higher structural stability during the charge and discharge process.

[0042] In one embodiment of the present application, the above-mentioned negative electrode sheet includes elastic conductive particles, negative electrode active materials, a binder and a conductive agent, including but not limited to, the binder is selected from any one or more of styrene-butadiene rubber, polyacrylic acid, polyisobutylene, nitrile rubber and styrene block copolymer, and the conductive agent is selected from any one or more of conductive carbon black, carbon nanotubes, vapor-grown carbon fibers and graphene.

[0043] In another typical embodiment of the present application, a battery is provided, including a positive electrode sheet, an electrolyte, and a negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet mentioned above.

[0044] Since the negative electrode sheet of the above lithium-ion battery contains the elastic conductive particles of the present application, the battery has higher cycle stability and capacity retention rate.

[0045] In a typical embodiment of the present application, a method for preparing a battery is provided:

[0046] Step 1: ball-mill the elastic microspheres and the raw materials of the conductive layer to mix and coat them to form elastic conductive particles.

[0047] Step 2: Evenly mix the elastic conductive particles, the negative electrode active material, the first conductive agent, and the first binder according to a set ratio, press them with the current collector to form an electrode with a corresponding surface density, and shape them to prepare a negative electrode sheet.

[0048] Step 3: Form the mixture and the current collector into a film, roll-press, and shape to prepare a negative electrode sheet.

[0049] Step 4: Evenly mix the positive electrode active material, the second conductive agent, and the second binder in a certain proportion, press them with the current collector to form an electrode with a corresponding surface density, and shape them to prepare a positive electrode sheet.

[0050] Step 5: The negative electrode sheet prepared in step 3, the ion-conducting electronic insulating layer, and the positive electrode sheet prepared in step 4 are assembled into a battery in a predetermined winding manner or stacked. The structure of the battery is as follows: Figure 2 As shown, a negative electrode sheet 100, an ion-conducting electronic insulating layer 200, and a positive electrode sheet 300 are stacked in sequence from top to bottom.

[0051] The preparation method of the present application is simple, does not require complicated equipment and processes, is compatible with existing battery production lines and processes, and is conducive to large-scale production applications.

[0052] Including but not limited to, the above-mentioned positive electrode active material is selected from any one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium iron manganese phosphate and lithium-rich manganese; the above-mentioned first conductive agent is selected from any one or more of conductive carbon black, carbon nanotubes, vapor-grown carbon fiber and graphene; the above-mentioned first binder is selected from any one or more of styrene-butadiene rubber, polyacrylic acid, polyisobutylene, nitrile rubber and styrene block copolymer; the above-mentioned second conductive agent is selected from any one or more of conductive carbon black, conductive graphite, carbon nanotubes, vapor-grown carbon fiber and graphene; the above-mentioned second binder is polyvinylidene fluoride and / or polytetrafluoroethylene.

[0053] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0054] Example 1

[0055] 1) The elastic particles and the raw materials of the conductive layer are ball-milled and mixed for 5 hours at a mass ratio of 99.5:0.5 to prepare elastic conductive particles with a D50 of 1.17 μm, wherein the material of the elastic particles is TPU, the average elastic modulus of the elastic conductive particles is 600 MPa, the average conductivity of the elastic conductive particles is 100000 S / m, and the raw material of the conductive layer is CNT.

[0056] 2) The elastic conductive particles are mixed with the negative electrode active material to obtain a mixture, and a binder of styrene-butadiene rubber and a conductive agent of carbon nanotubes are added to the mixture. The surface capacity is 4.00 mAh / cm 2 The negative electrode sheet is prepared by film forming, rolling and molding with a copper foil current collector, wherein the D50 of the negative electrode active material is 7 μm, the ratio of the D50 of the elastic conductive particles to the D50 of the negative electrode active material is 1:6, the gram capacity of the negative electrode active material is 700 mAh / g, the negative electrode active material is silicon oxygen carbon, and the mass ratio of the elastic conductive particles to the negative electrode active material is 1:20.

[0057] 3) Lithium nickel cobalt manganese oxide is mixed with polyvinylidene fluoride, conductive carbon black and carbon nanotubes, with a surface capacity of 3.75 mAh / cm 2 The positive electrode sheet is obtained by forming a film with the current collector, rolling and molding.

[0058] 4) The positive electrode, the ion-conducting electronic insulating layer, and the negative electrode are assembled into a battery in a stacked manner.

[0059] Example 2

[0060] The difference from Example 1 is that the material of the elastic particles is TPR, the average elastic modulus of the elastic conductive particles is 2.5 MPa, and a battery is finally obtained.

[0061] Example 3

[0062] The difference from Example 1 is that the material of the elastic particles is TPV, the average elastic modulus of the elastic conductive particles is 0.1 MPa, and a battery is finally obtained.

[0063] Example 4

[0064] The difference from Example 1 is that the material of the elastic particles is TPE, the average elastic modulus of the elastic conductive particles is 100 MPa, and a battery is finally obtained.

[0065] Example 5

[0066] The difference from Example 1 is that the material of the elastic particles is TPO, the average elastic modulus of the elastic conductive particles is 70 MPa, and a battery is finally obtained.

[0067] Example 6

[0068] The difference from Example 1 is that the material of the elastic particles is TPEE, the average elastic modulus of the elastic conductive particles is 80 MPa, and a battery is finally obtained.

[0069] Example 7

[0070] The difference from Example 1 is that the mass ratio of the elastic particles to the raw material of the conductive layer is 99:1, the raw material of the conductive layer is VGCF, the average conductivity of the elastic conductive particles is 1000 S / m, and a battery is finally obtained.

[0071] Example 8

[0072] The difference from Example 1 is that the D50 of the elastic conductive particles is 2.33 μm, and the ratio of the D50 of the elastic conductive particles to the D50 of the negative electrode active material is 1:3, and a battery is finally obtained.

[0073] Example 9

[0074] The difference from Example 1 is that the D50 of the elastic conductive particles is 7 μm, and the ratio of the D50 of the elastic conductive particles to the D50 of the negative electrode active material is 1:1, and a battery is finally obtained.

[0075] Example 10

[0076] The difference from Example 1 is that the mass ratio of the elastic conductive particles to the negative electrode active material is 1:10, and a battery is finally obtained.

[0077] Embodiment 11

[0078] The difference from Example 1 is that the mass ratio of the elastic conductive particles to the negative electrode active material is 1:5, and a battery is finally obtained.

[0079] Example 12

[0080] The difference from Example 1 is that the gram capacity of the negative electrode active material is 420 mAh / g, and a battery is finally obtained.

[0081] Example 13

[0082] The difference from Example 1 is that the gram capacity of the negative electrode active material is 500 mAh / g, and a battery is finally obtained.

[0083] Embodiment 14

[0084] The difference from Example 1 is that the ternary cathode material is mixed with polytetrafluoroethylene, sulfide electrolyte, and carbon nanotubes, and the surface capacity is 3.75 mAh / cm 2 The battery is finally obtained by forming a film, rolling and molding with the copper foil current collector.

[0085] Embodiment 15

[0086] The difference from Example 1 is that the D50 of the elastic conductive particles is 0.33 μm, the D50 of the negative electrode active material is 2 μm, and a battery is finally obtained.

[0087] Example 16

[0088] The difference from Example 1 is that the D50 of the elastic conductive particles is 5.83 μm, the D50 of the negative electrode active material is 35 μm, and a battery is finally obtained.

[0089] Embodiment 17

[0090] The difference from Example 1 is that the D50 of the elastic conductive particles is 0.88 μm, and the ratio of the D50 of the elastic conductive particles to the D50 of the negative electrode active material is 1:8, and a battery is finally obtained.

[0091] Embodiment 18

[0092] The difference from Example 1 is that the elastic particles are a mixture of first elastic particles and second elastic particles, the mass ratio of the first elastic particles to the second elastic particles is 1:4, the material of the first elastic particles is TPU, and the material of the second elastic particles is TPR, and a battery is finally obtained.

[0093] Embodiment 19

[0094] The difference from Example 1 is that the elastic particles are a mixture of first elastic particles and second elastic particles, the mass ratio of the first elastic particles to the second elastic particles is 1:1, the material of the first elastic particles is TPU, and the material of the second elastic particles is TPR, and a battery is finally obtained.

[0095] Comparative Example 1

[0096] The difference from Example 1 is that no elastic conductive particles are added to finally obtain a battery.

[0097] Comparative Example 2

[0098] The difference from Example 1 is that no elastic conductive particles are added, the gram capacity of the negative electrode active material is 500 mAh / g, and a battery is finally obtained.

[0099] Comparative Example 3

[0100] The difference from Example 1 is that no elastic conductive particles are added, the gram capacity of the negative electrode active material is 420 mAh / g, and a battery is finally obtained.

[0101] Comparative Example 4

[0102] The difference from Example 1 is that no CNT is added, the mass ratio of elastic particles to negative electrode active materials is 1:10, and a battery is finally obtained.

[0103] Comparative Example 5

[0104] The difference from Example 1 is that no elastic conductive particles are added, and the ternary positive electrode material is mixed with polytetrafluoroethylene, sulfide electrolyte, and carbon nanotubes. 2 The battery is finally obtained by forming a film, rolling and molding with the copper foil current collector.

[0105] Comparative Example 6

[0106] The difference from Example 1 is that the D50 of the elastic conductive particles is 14 μm, the ratio of the D50 of the elastic conductive particles to the D50 of the negative electrode active material is 1:0.5, and the mass ratio of the elastic conductive particles to the negative electrode active material is 1:4, and a battery is finally obtained.

[0107] Performance Testing

[0108] The battery prepared in the embodiment and comparative example is connected to the charge and discharge channel, and the battery is activated. The activation steps used are: 0.01C constant current charging for 10 hours, 0.05C constant current charging to 4.2V, switching to constant voltage charging until the current drops to 0.02C, standing for 1 hour, and discharging at 0.1C constant current to 2.5V. The battery is externally pressurized, 1C constant current and constant voltage charging to 4.2V, and the thickness of the battery at full charge and empty charge is recorded, and the expansion rate is calculated = (full charge thickness / empty charge thickness) * 100%. The above battery is externally pressurized, and the charge and discharge cycle is carried out 100 times with a cut-off voltage of 1C current 4.2~2.5V to measure the thickness of the battery at full charge and the capacity retention rate. The results of the first week charge and discharge expansion rate, 100-week cycle retention rate, and 100-week cycle full charge thickness / first week full charge thickness of the battery prepared in the embodiment and comparative example are shown in Table 1.

[0109] Table 1

[0110]

[0111]

[0112] In Table 1, since the gram capacity of the negative electrode active material has a greater impact on the battery expansion, the gram capacity of the negative electrode active material in Example 12, Example 13, Comparative Example 2 and Comparative Example 3 is much smaller than the gram capacity of the negative electrode active material in Example 1. Therefore, the battery expansion rate in Example 12, Example 13, Comparative Example 2 and Comparative Example 3 changes less and the cycle capacity retention rate is higher. Example 1 is a liquid battery, and Example 14 and Comparative Example 5 are solid-state batteries. Due to the different battery systems, the change in battery expansion rate and cycle capacity retention rate are quite different.

[0113] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0114] Adding elastic conductive particles to the negative electrode active material helps to absorb and disperse the stress caused by the volume change of the negative electrode active material during the charge and discharge process, thereby helping to reduce the expansion rate of the electrode, and then helping to reduce the attenuation of the negative electrode capacity. By controlling the ratio of the D50 of the elastic conductive particles to the D50 of the negative electrode active material to 1:1 to 8, it helps to further absorb and relieve the volume expansion stress generated by the negative electrode active material during the charge and discharge process. By controlling the mass proportion of elastic conductive particles in the negative electrode active material to not more than 16.67%, the stress relief effect is guaranteed and excessive impact on the battery energy density is avoided. In short, the present application helps to absorb and disperse the stress caused by the volume change of the negative electrode active material during the charge and discharge process by introducing elastic conductive particles, thereby helping to improve the cycle stability and capacity retention rate of the battery.

[0115] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes a negative electrode active material and elastic conductive particles, the ratio of D50 of the elastic conductive particles to D50 of the negative electrode active material is 1:1-8, and the mass proportion of the elastic conductive particles in the negative electrode active material does not exceed 16.67%.

2. The negative electrode material according to claim 1, characterized in that The ratio of D50 of the elastic conductive particles to D50 of the negative electrode active material is 1:3-6.

3. The negative electrode material according to claim 1, characterized in that The mass ratio of the elastic conductive particles to the negative electrode active material is 1:10-20.

4. The negative electrode material according to any one of claims 1 to 3, characterized in that The average elastic modulus of the elastic conductive particles is 0.1-600 MPa; and / or the average electrical conductivity of the elastic conductive particles is 1000-100000 S / m.

5. The negative electrode material according to any one of claims 1 to 3, characterized in that The elastic conductive particles include elastic particles and a conductive layer coated on the surface of the elastic particles, and the mass proportion of the conductive layer in the elastic conductive particles does not exceed 1%.

6. The negative electrode material according to claim 5, characterized in that The material of the elastic particles is selected from any one or more of thermoplastic elastomers, thermoplastic rubbers, thermoplastic vulcanized rubbers, thermoplastic polyurethane elastomers, thermoplastic polyolefin elastomers and thermoplastic polyester elastomers; and / or the material of the conductive layer is selected from any one or more of carbon nanotubes, vapor-grown carbon fibers and graphene.

7. The negative electrode material according to claim 5, characterized in that The elastic particles include first elastic particles and second elastic particles, the mass ratio of the first elastic particles to the second elastic particles is 1:1-4, the material of the first elastic particles is thermoplastic polyurethane elastomer, and the material of the second elastic particles is thermoplastic rubber.

8. The negative electrode material according to any one of claims 1 to 3, characterized in that The D50 of the negative electrode active material is 2 μm to 35 μm; and / or, the gram capacity of the negative electrode active material is not less than 420 mAh / g; and / or, the negative electrode active material is selected from any one or more of silicon oxygen carbon, silicon carbon and micron silicon.

9. A negative electrode sheet, characterized in that: The negative electrode sheet contains the negative electrode material according to any one of claims 1 to 8.

10. A battery comprising a positive electrode, an electrolyte, and a negative electrode, characterized in that: The negative electrode sheet is the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Cathode pole piece, preparation method for cathode pole piece and lithium ion battery

    CN106848190A

  • Silicon-based negative electrode conductive paste and preparation method thereof, and preparation method of silicon-based negative electrode sheet

    CN115663188A

  • Composite powder capable of increasing silicon content through secondary compounding and preparation method and application of composite powder

    CN116169277A